“What About Automated Pain Recognition for Routine Clinical Use?” A Survey of Physicians and Nursing Staff on Expectations, Requirements, and Acceptance - Walter, Steffen; Gruss, Sascha; Frisch, Stephan; Liter, Joseph; Jerg-Bretzke, Lucia; Zujalovic, Benedikt; Barth, Eberhard (Frontiers in Medicine, 2020)
Background: Over the last 12 years, the fundamentals of automated pain recognition using artificial intelligence (AI) algorithms have been investigated and optimized. The main target groups are patients with limited communicative abilities. To date, the extent to which anesthetists and nurses in intensive care units would benefit from an automated pain recognition system has not been investigated. Methods: N = 102 clinical employees were interviewed. To this end, they were shown a video in which the visionary technology of automated pain recognition, its basis and goals are outlined. Subsequently, questions were asked about: (1.) the potential benefit of an automated pain recognition in clinical context, (2.) preferences with regard to the modality used (physiological, paralinguistic, video-based, multimodal), (3.) the maximum willingness to invest, (4.) preferences concerning the required pain recognition rate and finally (5.) willingness to use automated pain recognition. Results: The respondents expect the greatest benefit from an automated pain recognition system to be "to avoid over- or undersupply of analgesics in patients with limited communicative abilities", a total of 50% of respondents indicated that they would use automated pain recognition technology, 32.4% replied with “perhaps” and 17.4% would not use it. Conclusion: Automated pain recognition is, in principle, accepted by anesthetists and nursing staff as a possible new method, with expected benefits for patients with limited communicative skills. However, studies on automated pain recognition in a clinical environment and proof of its acceptance and practicability are absolutely necessary before such systems can be implemented.